Proton and carbon ion radiotherapy for primary brain tumors and tumors of the skull base - Combs, Stephanie E.; Kessel, Kerstin; Habermehl, Daniel; Haberer, Thomas; Jaekel, Oliver; Debus, Juergen (Acta Oncologica, 2013)
To analyze clinical concepts, toxicity and treatment outcome in patients with brain and skull base tumors treated with photons and particle therapy. Material and methods. In total 260 patients with brain tumors and tumors of the skull base were treated at the Heidelberg Ion Therapy Center (HIT). Patients enrolled in and randomized within prospective clinical trials as well as bony or soft tissue tumors are not included in this analysis. Treatment was delivered as protons, carbon ions, or combinations of photons and a carbon ion boost. All patients are included in a tight follow-up program. The median follow-up time is 12 months (range 2-39 months). Results. Main histologies included meningioma (n = 107) for skull base lesions, pituitary adenomas (n = 14), low-grade gliomas (n = 51) as well as high-grade gliomas (n = 55) for brain tumors. In all patients treatment could be completed without any unexpected severe toxicities. No side effects > CTC Grade III were observed. To date, no severe late toxicities were observed, however, for endpoints such as secondary malignancies or neurocognitive side effects follow-up time still remains too short. Local recurrences were mainly seen in the group of high-grade gliomas or atypical meningiomas; for benign skull base meningiomas, to date, no recurrences were observed during follow-up. Conclusion. The specific benefit of particle therapy will potentially reduce the risk of secondary malignancies as well as improve neurocognitive outcome and quality of life (QOL); thus, longer follow-up will be necessary to confirm these endpoints. Indication-specific trials on meningiomas and gliomas are underway to elucidate the role of protons and carbon ions in these indications. © 2013 Informa Healthcare.
CRIS-Team Scopus Importer:2023-03-08